2015
DOI: 10.1088/1674-1056/24/4/047502
|View full text |Cite
|
Sign up to set email alerts
|

Model of hybrid interfacial domain wall in ferromagnetic/antiferromagnetic bilayers

Abstract: A general model of a hybrid interfacial domain wall (HIDW) in ferromagnetic/antiferromagnetic exchange biased bilayers is proposed, where an interfacial domain wall is allowed to extend into either the ferromagnetic or antiferromagnetic layer or across both. The proposition is based on our theoretical investigation on thickness and field dependences of ferromagnetic domain wall (FMDW) and antiferromagnetic domain wall (AFDW), respectively. Good match of the simulation to the hysteresis loops of a series of NiF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…More recently, Morales et al proposed that springlike FM domain walls, which are parallel to the AFM/FM interface, exist in EB systems [10]. The relevant micromagnetic simulation results also supported a hybrid interfacial domain wall extending into AFM and FM layers [16,17]. The spring spin structure caused by opposite pinning directions in AFM/FM/AFM trilayers can be distributed through the total 50-nm FM layer [17], suggesting that the detection of depth-dependent magnetic profiles or spin structure of FM layer in EB systems is not trivial.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, Morales et al proposed that springlike FM domain walls, which are parallel to the AFM/FM interface, exist in EB systems [10]. The relevant micromagnetic simulation results also supported a hybrid interfacial domain wall extending into AFM and FM layers [16,17]. The spring spin structure caused by opposite pinning directions in AFM/FM/AFM trilayers can be distributed through the total 50-nm FM layer [17], suggesting that the detection of depth-dependent magnetic profiles or spin structure of FM layer in EB systems is not trivial.…”
Section: Introductionmentioning
confidence: 89%
“…Two soft FM materials (NiFe and Fe) are selected to check whether the twisted configurations always exist and influence the EB properties in the common soft FM materials. The FM magnetic parameters for the simulations were A NiFe = 1.2 × 10 −6 erg • cm −1 [26,29] and K NiFe = 2 × 10 3 erg • cm −3 [26,30], A Fe = 1.49 × 10 −6 erg • cm −1 [31] and K Fe = 4.72 × 10 5 erg • cm −3 [31]. The AF magnetic parameters A AF = 2.4 × 10 −6 erg • cm −1 and K AF = 2 × 10 6 erg • cm −3 were determined for anchoring the AF spins completely during magnetization, and the interface magnetic parameter…”
Section: Methodsmentioning
confidence: 99%
“…has been confirmed experimentally by Morales et al [25] in FeF 2 (70 nm)/NiFe(t FM ) bilayers. Using a twisted domain-wall model [25,26], the low-temperature magnetization and EB behaviors were fitted well. Furthermore, Morales et al [25] found an anomalous thermal dependence of EB but were not able to give an illustrated interpretation due to the exclusion of temperature dependence in their model.…”
Section: Fmmentioning
confidence: 99%
“…As for FM/SG/AFM trilayers, the J IF term in equation (6) does not exist. Considering common FM materials such as permalloy, nickel metal, and iron metal [26,[40][41][42][43], an average value of their exchange constants is set as the realistic FM exchange constant by J FM =6.53 erg cm −2 . As a result, in the simulation J FM is scaled by J xJ .…”
Section: S S S Smentioning
confidence: 99%